The relative potential contribution of volume load and vascular mechanisms to hypertension in non-dialysis and dialysis chronic kidney disease patients - Tade, Grace; Hsu, Hon-Chun; Robinson, Chanel; Dlongolo, Noluntu; Teckie, Gloria; Solomon, Ahmed; Dessein, Patrick Hector (Frontiers in Cardiovascular Medicine, 2024)
Background: Hypertension is highly prevalent and particularly difficult to treat adequately in patients with chronic kidney disease (CKD). The relative contribution of volume overload and vascular mechanisms to blood pressure measures in CKD and whether these effects differ in non-dialysis compared to dialysis patients is unknown. Methods: We determined the potential impact of volume load (stroke volume) and vascular mechanisms (inverse of total arterial compliance (inv TAC) and systemic vascular resistance (SVR)) on mean and brachial and aortic systolic blood pressures in 67 non-dialysis and 48 dialysis chronic kidney disease (CKD) patients. Relationships were determined in confounder adjusted regression models. Results: Stroke volume (p value=0.003) was more strongly associated with mean arterial pressure than SVR (p value= 0.9) (p value for difference=0.03). When stroke volume and SVR were entered in the same regression model (model R 2 =0.324), they contributed equally to the variation in mean arterial pressure (p value for difference=0.5). Stroke volume (p value<0.002) and inv TAC (p value<0.001) contributed equally to the variation in systolic pressures (p value for difference>0.9). When stroke volume and inv TAC were entered in the same regression model (model R 2 =0.752 to 0.765), they contributed equally to the variation in systolic blood pressures (p value for difference=0.7). Stroke volume, TAC and SVR were similar (p value>0.5) and associated to the same extent with blood pressure measures in non-dialysis and dialysis CKD patients (p value for difference>0.1). In receiver operator characteristic curve analysis, uncontrolled elevated systolic blood pressure was determined by stroke volume (p value=0.005) and inv TAC (p value=0.03) but not SVR (p value=0.8). The calculated power of the study was 0.999 based on α=0.05. Conclusions: The present investigation suggests that both volume load and vascular mechanisms should be considered in the management of hypertension among patients with CKD. The extent and relative potential impact of volume load and vascular mechanisms on blood pressure measures are as large in non-dialysis compared to dialysis CKD patients. KEYWORDS chronic kidney disease; volume load; stroke volume; total arterial compliance; systemic vascular resistance; blood pressure determinants